2-(2,6-Dichlorophenyl)-1-pentyl-4,5-diphenyl-1H-imidazole - Mehmet Akkurt; Shaaban K. Mohamed; Kuldip Singh; Adel A. Marzouk; Antar A. Abdelhamid (Acta Crystallographica Section E, 2013)
The title compound, C26H24Cl2N2, crystallizes with two independent molecules (1 and 2) in the asymmetric unit. In molecule 1, the two phenyl and 2,6-dichlorophenyl rings are inclined to the imidazole ring at angles of 74.12 (14), 26.13 (14) and 67.30 (14)°, respectively. In molecule 2, due to the different molecular environment in the crystal, the corresponding angles are different, viz. 71.72 (15), 16.14 (15) and 80.41 (15)°, respectively. In the crystal, molecules 1 and 2 are linked by C—H...Cl interactions, and inversion-related 2 molecules are linked by C—H...π interactions. There are no other significant intermolecular interactions present.